Ocular therapeutics - Garg, Ashok (New Delhi : Jaypee-Highligts Medical Publishers, 2013)
Pone al día a los médicos con los últimos avances en fármacos oftálmicos, analizando la fisiología del ojo, la administración de fármacos, el papel fundamental de la terapéutica ocular, la aplicación de fármacos oftálmicos y desarrollos futuros.
.Brings practitioners up to date with the latest advances in ophthalmic drugs, discussing physiology of the eye, drug administration, the fundamental role of ocular therapeutics, the application of ophthalmic drugs and future developments.
CONTENTS Section 1: Fundamentals and Preliminary Considerations in Ocular Therapeutics 2.Section 2. Applied ocular therapeutics in ophthalmic surgery 3. Section 3. Recent advances in ocular therapeutics
Keywords: ENFERMEDADES DE LOS OJOS; FARMACOLOGÍA OCULAR; EYE DISEASES